2011
DOI: 10.1103/physrevlett.107.174803
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a High-Field Short-Period Superconducting Helical Undulator Suitable for Future TeV-Scale Linear Collider Positron Sources

Abstract: The first demonstration of a full-scale working undulator module suitable for future TeV-scale positron-electron linear collider positron sources is presented. Generating sufficient positrons is an important challenge for these colliders, and using polarized e(+) would enhance the machine's capabilities. In an undulator-based source polarized positrons are generated in a metallic target via pair production initiated by circularly polarized photons produced in a helical undulator. We show how the undulator desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Further developments of planar SCUs for 3GSRs are ongoing at ANKA (Boffo et al 2011), APS (Ivanyushenkov et al 2013), DIAMOND (Clarke et al 2013), and other places. SCUs are evaluated for future light sources as well, and they are objects of extensive studies in high-energy accelerator projects such as the ILC (Scott et al 2011).…”
Section: Superconducting Undulatorsmentioning
confidence: 99%
“…Further developments of planar SCUs for 3GSRs are ongoing at ANKA (Boffo et al 2011), APS (Ivanyushenkov et al 2013), DIAMOND (Clarke et al 2013), and other places. SCUs are evaluated for future light sources as well, and they are objects of extensive studies in high-energy accelerator projects such as the ILC (Scott et al 2011).…”
Section: Superconducting Undulatorsmentioning
confidence: 99%
“…A positron yield of 1.5 e + /e − is desired. Prototype studies [2] showed that superconducting undulators with period λ = 11.5 mm and K factors up to 0.92 are possible.…”
Section: Introductionmentioning
confidence: 99%
“…Copper and tungsten are the considered materials for masks. The uncertainty of the undulator B-field used in the realistic case for the studies here is based on the size of the B-field errors measured from helical undulator prototypes [2].…”
Section: Introductionmentioning
confidence: 99%
“…The undulator field strength, although not a determining parameter for the wavelength, must be sufficiently high to maintain the brilliance of the radiation, especially that of the harmonics, and the gain of amplification in FELs at a high level with a short-period undulator and low-energy electron beam. In addition, the use of multi-MeV gamma rays from highfield, short-period undulators to generate polarized positron beams via particle-antiparticle pair production in future linear colliders has been proposed [9].…”
Section: Introductionmentioning
confidence: 99%